2021
DOI: 10.1093/cid/ciab437
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Peripheral Blood Neutrophil Activation Phenotypes and Neutrophil Extracellular Trap Formation in Critically Ill Coronavirus Disease 2019 (COVID-19) Patients: A Case Series and Review of the Literature

Abstract: Background Increased inflammation has been well defined in COVID-19, while definitive pathways driving severe forms of this disease remain uncertain. Neutrophils are known to contribute to immunopathology in infections, inflammatory diseases and acute respiratory distress syndrome (ARDS), a primary cause of morbidity and mortality in COVID-19. Changes in neutrophil function in COVID-19 may give insight into disease pathogenesis and identify therapeutic targets. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 38 publications
7
84
1
3
Order By: Relevance
“…While IgA-induced NETosis would have a beneficial component in mucosal linings by preventing viral entry, it would be ineffective or even harmful in other locations, as neutrophils in the bloodstream perform their most protective phagocytic functions in response to IgG antibodies. Many studies have shown that NETosis is a defining feature of severe disease 49,72,73 , and here, we demonstrate that NETosis can be strongly induced by IgA antibodies, which may be the dominant effector function occurring in patients with high ratios of IgA1-to-IgG1 antibodies in plasma. Several potential therapeutics have been suggested for use in autoimmune disease contexts aimed at inhibiting NETosis such as PAD4 inhibition or administration of recombinant human thrombomodulin 74 , and similar strategies could be applied to NETosis in the context of severe COVID-19.…”
Section: Discussionsupporting
confidence: 67%
“…While IgA-induced NETosis would have a beneficial component in mucosal linings by preventing viral entry, it would be ineffective or even harmful in other locations, as neutrophils in the bloodstream perform their most protective phagocytic functions in response to IgG antibodies. Many studies have shown that NETosis is a defining feature of severe disease 49,72,73 , and here, we demonstrate that NETosis can be strongly induced by IgA antibodies, which may be the dominant effector function occurring in patients with high ratios of IgA1-to-IgG1 antibodies in plasma. Several potential therapeutics have been suggested for use in autoimmune disease contexts aimed at inhibiting NETosis such as PAD4 inhibition or administration of recombinant human thrombomodulin 74 , and similar strategies could be applied to NETosis in the context of severe COVID-19.…”
Section: Discussionsupporting
confidence: 67%
“…COVID-19 patients are reported to have increased serum IL-8 levels that correlate with disease severity, but the cellular source(s) have not been definitively identified [ 20 , 38 , 39 ]. Neutrophils are a source of IL-8 production, and neutrophil IL-8 production and release may result in amplification of systemic inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the presence of NET fragments or cell-free DNA in the plasma of COVID-19 patients [14][15][16][17], and post-mortem analysis reveals the presence of NETs in lung tissue of COVID-19 patients [17][18][19]. An elevation in cytokines, including IL-8, has also been observed in the plasma of COVID-19 patients [20], but the cellular source is not clear. Neutrophil elastase has been implicated in the pathogenesis of lung disease, and elastase inhibitors have been used in clinical trials with mixed results [9,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has a longstanding interest in the biology and pathobiology of NETs in animal models of infectious diseases such as necrotizing fasciitis 10 and bacterial pneumonia 11 , and recently we studied NET phenotypes in critically ill patients with COVID-19 12 . In parallel, we have examined how NETosis is modulated by common medications including statins 13 , tamoxifen 14 , desferoxamine 15 , and propofol 16 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%